An audit of the reliability of influenza vaccination and medical information extracted from eHealth records in general practice - Regan, Annette; Gibbs, R.; Effler, P. (Elsevier, 2018)
To evaluate the reliability of information in general practice (GP) electronic health records (EHRs), 2100 adult patients were randomly selected for interview regarding the presence of specific medical conditions and recent influenza vaccination. Agreement between self-report and data extracted from EHRs was compared using Cohen’s kappa coefficient (k) and interpreted in accordance with Altman’s Kappa Benchmarking criteria; 377 (18%) patients declined participation, and 608 (29%) could not be contacted. Of 1115 (53%) remaining, 856 (77%) were active patients (≥3 visits to the GP practice in the last two years) who provided complete information for analysis. Although a higher proportion of patients self-reported being vaccinated or having a medical condition compared to the EHR (50.7% vs 36.9%, and 39.4% vs 30.3%, respectively), there was “good” agreement between self-report and EHR for both vaccination status (κ = 0.67) and medical conditions (κ = 0.66). These findings suggest EHR may be useful for public health surveillance.